MANAJEMEN KELAS KHUSUS OLAHRAGA UNTUK BRANDING MTs NEGERI 6 SRAGEN: Integrasi Inovasi Olahraga dalam Branding Sekolah: Mendorong Pengembangan Karakter dan Citra Lembaga pada Pendidikan Berbasis Agama - Suryono Suryono; Baidi Baidi (CV. Media Publikasi Profesional, 2026)
In an increasingly competitive educational landscape, sports is no longer merely a supplementary physical activity but a strategic instrument capable of transforming a school's identity and appeal. The penetration of interest-based innovations, such as specialized sports classes, has become a primary catalyst in building the unique reputation of religious-based educational institutions. This study aims to examine sports class management strategies in a madrasah and their impact on institutional branding. Adopting a qualitative case study approach, data were gathered through in-depth interviews with the madrasah principal, program coordinator, sports teachers, and students. The results identified four main themes: (1) sports class management as educational innovation, (2) the role of sports in character building, (3) implementation challenges, and (4) community contributions in strengthening branding. The findings indicate that sports integration effectively facilitates comprehensive character development while reinforcing the madrasah’s position as a progressive institution. Synergistic stakeholder support is a crucial factor in ensuring program sustainability and reputation enhancement. This research theoretically expands the educational management paradigm by integrating the sociology of sports into school marketing strategies. Practically, it formulates a specialized class management model that other madrasahs can adopt to optimize local resources, creating a strong differentiation value within the currently saturated educational market.